Prediction of the Broadband Noise Radiated from a Fan Rotor of a High-Bypass Ratio Turbofan Engine: Cruise Condition. (February 2014) - El-Sayed, Ahmed F.; Kamal, Radwan M.; Ahmed, Hamdy A.
The purpose of this study is the prediction of the broadband noise generated by the fan rotor of a high bypass ratio turbofan engine at cruise condition. A numerical investigation of the unsteady aerodynamics of a fan rotor was described, with emphasis on acoustics. Three case studies were examined; namely, design point, a chocked point, and a near surge point. It was found that, the dominant broadband noise mechanisms are due to, interaction of turbulence of the incoming flow with the engine casing and nose, interaction of the turbulent boundary layers on the rotor blades with their trailing edges, and interaction of the rotating blade with the turbulence in the incoming flow. The most important noise source was the interaction of the turbulent boundary layers on the rotor blades with their trailing edges. Chocked case scored the highest noise level as it has the maximum turbulent kinetic energy levels, maximum mass flow rate and thus maximum relative Mach number. Near-surge case has the lowest noise level except at the lower part of the suction side of the rotor where the reverse flow and vortices caused higher levels of noise.